Tomotherapy and other innovative IMRT delivery systems. - Fenwick, J; Tomé, W; Soisson, E; Mehta, M; Rock Mackie, T (2006)
Fixed-field treatments, delivered using conventional clinical linear accelerators fitted with multileaf collimators, have rapidly become the standard form of intensity-modulated radiotherapy (IMRT). Several innovative nonstandard alternatives also exist, for which delivery and treatment planning systems are now commercially available. Three of these nonstandard IMRT approaches are reviewed here: tomotherapy, robotic linear accelerators (CyberKnife, Accuray Inc., Sunnyvale, CA), and standard linear accelerators modulated by jaws alone or by their jaws acting together with a tertiary beam-masking device. Rationales for the nonstandard IMRT approaches are discussed, and elements of their delivery system designs are briefly described. Differences between fixed-field IMRT dose distributions and the distributions that can be delivered by using the nonstandard technologies are outlined. Because conventional linear accelerators are finely honed machines, innovative design enhancement of one aspect of system performance often limits another facet of machine capability. Consequently the various delivery systems may prove optimal for different types of treatment, with specific machine designs excelling for disease sites with specific target volume and normal structure topologies. However it is likely that the delivery systems will be distinguished not just by the optimality of the dose distributions they deliver, but also by factors such as the efficiency of their treatment process, the integration of their onboard imaging systems into that process, and their ability to measure and minimize or compensate for target movement, including the effects of respiratory motion.